Global patterns of nutrient limitation in soil microorganisms - Yongxing Cui; Shushi Peng; Matthias C. Rillig; Tessa Camenzind; Manuel Delgado-Baquerizo; Cesar Terrer; Xiaofeng Xu; Maoyuan Feng; Mengjie Wang; Linchuan Fang; Biao Zhu; Enzai Du; et al. (Proceedings of the National Academy of Sciences, 2025)
The availability of nitrogen (N) and phosphorus (P) is essential for soil microbial activity and growth, yet global patterns of N and P limitation in soil microbial metabolism remain largely unknown. We modeled ecoenzyme stoichiometry data from 5,259 field observations of natural ecosystems to assess microbial N and P limitation in global surface soils. We found that microbial P limitation, which was especially strong at low latitudes, was more prevalent globally than microbial N limitation, which prevailed in cold environments. We also found widespread N and P colimitation in soil microorganisms in the tropics, contradicting the long-held paradigm that P, and not N, is the primary limiting nutrient at low latitudes. This colimitation could be attributable to elevated microbial N demand for the synthesis of P-acquiring enzymes under P limitation. Upscaling (0.1 × 0.1° spatial resolution) suggested that soil microorganisms were limited by N and P in 39% and 57%, respectively, of natural terrestrial surface areas, with 21% of areas with N and P colimitation. As a global assessment of spatial variation in microbial N and P limitation, our results highlight the importance of N availability in supporting microbial P acquisition at low latitudes and improve our understanding of microbial nutrient limitation on a global scale.